2014
DOI: 10.1111/jora.12142
|View full text |Cite
|
Sign up to set email alerts
|

Latino Students' Transition to Middle School: Role of Bilingual Education and School Ethnic Context

Abstract: Participants were 204 academically at-risk Latino students recruited into a study when in first grade and followed for 9 years. Using piecewise latent growth curve analyses, we investigated trajectories of teacher-rated behavioral engagement and student-reported school belonging during elementary school and middle school and the association between trajectories and enrollment in bilingual education classes in elementary school and a change in school ethnic congruence across the transition to middle school. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
2
10
0
1
Order By: Relevance
“…For example, Akos and Galassi () found that Latinos perceived the middle school transition as significantly more challenging than did their White and African American peers. Consistent with these perceptions, previous research also documented a significant drop in school belonging, achievement, and engagement when Latinos transitioned to middle school (Espinoza & Juvonen, ; Hughes, Im, Kwok, Cham, & West, ; Wampler, Munsch, & Adams, ). Understanding and contextualizing the middle school transition experiences of Latinos is pivotal to help curtail their risk of academic failure in middle school and subsequent school dropout (Ream & Rumberger, ).…”
Section: The Current Studysupporting
confidence: 56%
See 3 more Smart Citations
“…For example, Akos and Galassi () found that Latinos perceived the middle school transition as significantly more challenging than did their White and African American peers. Consistent with these perceptions, previous research also documented a significant drop in school belonging, achievement, and engagement when Latinos transitioned to middle school (Espinoza & Juvonen, ; Hughes, Im, Kwok, Cham, & West, ; Wampler, Munsch, & Adams, ). Understanding and contextualizing the middle school transition experiences of Latinos is pivotal to help curtail their risk of academic failure in middle school and subsequent school dropout (Ream & Rumberger, ).…”
Section: The Current Studysupporting
confidence: 56%
“…All of these findings suggest that, like exposure to bilingual education in the Hughes et al. () study, there may be social and academic benefits to ethnic diversity in middle school that might buffer some of the challenges of declining ethnic group representation across the transition to middle school.…”
Section: The Current Studymentioning
confidence: 91%
See 2 more Smart Citations
“…Example items include “tries hard to do well in school”; “participates in class discussion”; and pays attention in class.” Teachers indicated the extent to which each statement was true on a 1 ( Not true at all ) to 4 ( Very true ) scale. The scale demonstrates good factorial validity (Hughes, Im, Cham, Kwok, & West, 2014). The internal consistency reliabilities( α ) at baseline and grade 9 were .92 and .91, respectively.…”
Section: Methodsmentioning
confidence: 99%